2020
DOI: 10.3390/jcm9124082
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Nutritional Status in Pulmonary Tuberculosis: Longitudinal Changes in BMI According to Acid-Fast Bacilli Smear Positivity

Abstract: Malnutrition is closely associated with pulmonary tuberculosis (PTB). However, changes before and after treatment remain unclear. We aimed to investigate the longitudinal changes in nutritional status from treatment to follow-up of TB in 215 PTB cases in South Korea. First, we evaluated the trend in body mass index (BMI) from the time of diagnosis to a 2-year follow-up. Second, we compared the BMIs of our cases with 5694 controls who participated in a Korean national survey after treatment. During the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
(23 reference statements)
1
8
0
1
Order By: Relevance
“…Some study showed that there was significant variation in BMI of PTB patients -mostly decreased BMI below normal. 14 In the present study there is highly significant decrease of serum zinc concentration in case group compared with control group that showed similarity with Sharda and Bhandari., Karyadiet et al, and Koyanagi et al,. 8,15,16 Redistribution of zinc in the liver plays an important role and Metallothionein that bind with zinc and draw away from circulating pool done by IL-1 that explain MTB use zinc for growth and reproduction.…”
Section: Discussionsupporting
confidence: 85%
“…Some study showed that there was significant variation in BMI of PTB patients -mostly decreased BMI below normal. 14 In the present study there is highly significant decrease of serum zinc concentration in case group compared with control group that showed similarity with Sharda and Bhandari., Karyadiet et al, and Koyanagi et al,. 8,15,16 Redistribution of zinc in the liver plays an important role and Metallothionein that bind with zinc and draw away from circulating pool done by IL-1 that explain MTB use zinc for growth and reproduction.…”
Section: Discussionsupporting
confidence: 85%
“…Low BMI has a substantial impact on TB development [ 24 , 40 ], and weight loss during TB treatment is associated with increased mortality [ 41 ]. In addition, TB survivors are known to have lower BMI than those without TB [ 42 ]. However, the long-term effect of low BMI on mortality in TB survivors is not well known, and our study provided informative data showing the persistent long-term effect of low BMI on mortality in TB survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Chiang et al showed that weight gain optimizes TB treatment in children with tuberculosis [15]. In line with that study, a study using data in the TB clinic of Hallym University Kangdong Sacred Heart Hospital, Seoul, Korea, showed that nutritional status significantly correlated with the optimization of treatment for pulmonary tuberculosis (PTB) patients [16]. In addition, oral nutritional supplement consumption such as food, protein/energy supplements, or micronutrients can increase their body weight [5] [17] [18].…”
Section: Introductionmentioning
confidence: 87%
“…Fulfillment of nutritional adequacy and development of the adaptive immune system in children are determined by exclusive breastfeeding from birth to 6 months of age [11] [12][13] [14]. Conversely, children with tuberculosis are at risk of experiencing malnutrition due to decreased appetite and intake, nutrient malabsorption, and increased metabolic [7][15] [16]. Chiang et al showed that weight gain optimizes TB treatment in children with tuberculosis [15].…”
Section: Introductionmentioning
confidence: 99%